234k views
3 votes
Apply the distributive property to create an equivalent expression. 4\left(3 + \dfrac14c - \dfrac12d\right) =4(3+ 4 1 ​ c− 2 1 ​ d)=

2 Answers

2 votes

answer = 12+c-2d

.......................................................

User Quill
by
5.8k points
3 votes

Answer:

The equivalent expression is
12+c-2d

Explanation:

Using the distributive property we expand the expression


4\left(3 + \frac14c - \frac12d\right)

as follows:


4\left(3 + \frac14c - \frac12d\right)=(4*3)+(4*(1)/(4) c)-(4*(1)/(2) d)


=(12)+(c)-(2d)


=\boxed{ 12+c-2d}

which is the equivalent expression.

User Ossmalpha
by
5.9k points